2015
DOI: 10.1155/2015/579147
|View full text |Cite
|
Sign up to set email alerts
|

A New Twist to a Chronic HCV Infection: Occult Hepatitis C

Abstract: Background. The prevalence of occult hepatitis C infection (OCI) in the population of HCV-RNA negative but anti-HCV positive individuals is presently unknown. OCI may be responsible for clinically overt recurrent disease following an apparent sustained viral response (SVR) weeks to years later. Purpose. To review the available current literature regarding OCI, prevalence, pathogenic mechanisms, clinical characteristics, and future directions. Data Sources. Searching MEDLINE, article references, and national an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 128 publications
1
36
0
Order By: Relevance
“…Our findings provide further insight into the mechanisms of virus pathogenesis and may be used to design DAA-based therapeutic regimens because current treatments, including combinations of two DAAs, are still not fully successful, especially at advanced chronic stages with fibrosis [32]. Moreover, the virus can persist in liver and blood cells even in cured patients with HCV RNA undetectable in the peripheral blood and normal liver enzyme tests [33], and risk of fibrosis, cirrhosis, and liver cancer remains high [34]. A current trend in treating virus diseases is identifying cell targets for therapy and designing drugs to block virus replication.…”
Section: Discussionmentioning
confidence: 86%
“…Our findings provide further insight into the mechanisms of virus pathogenesis and may be used to design DAA-based therapeutic regimens because current treatments, including combinations of two DAAs, are still not fully successful, especially at advanced chronic stages with fibrosis [32]. Moreover, the virus can persist in liver and blood cells even in cured patients with HCV RNA undetectable in the peripheral blood and normal liver enzyme tests [33], and risk of fibrosis, cirrhosis, and liver cancer remains high [34]. A current trend in treating virus diseases is identifying cell targets for therapy and designing drugs to block virus replication.…”
Section: Discussionmentioning
confidence: 86%
“…Numerous reports indicated that the unfavorable IFNL3 and IFNL4 genotypes are associated with reduced response to pegIFN‐α/RBV therapy and augmented the frequency of HCV infection in PBMCs . The impact of IFNL3 rs12979860 genotypes on OCI is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The HCV genome is identified by liver biopsy using tissue samples or PBMCs (in 70% of cases) in patients with undetectable HCV genome in serum, representing the gold standard to identify OCI …”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, HCV detected in serum or plasma is clinical therapy evidence, but as more and more OCI issues are being discussed, the concern of clinical relevance and influence on the patients has become of great importance [27]. In a follow-up study of people undergoing phlebotomy therapy [28], 6 subjects with OCI were monitored, with only 2 showing detectable HCV infection in PBMCs at 11 and 13 months of follow-up, demonstrating a persistent infection.…”
Section: Discussionmentioning
confidence: 99%